Effectiveness of Legislative Performance on Community Satisfaction Macassar City Council - Malik, Sahruddin; Hatim, Husnul (Cendekiawan Indonesia Timur, 2024)
The purpose of this study was to determine the effectiveness of the performance of legislative members on community satisfaction and the factors that influence the performance carried out by legislative members in order to fulfill community satisfaction as constituents in increasing community participation. The research method used is descriptive research with a qualitative approach. Data collection techniques through observation, interviews and documentation. The data source, namely primary data, is data obtained directly by researchers from informants at the research location through interviews with legislative member informants.The results of field research show that the effectiveness of the performance of legislative members on community satisfaction is characterized by community participation in supporting every law that has been decided. This can be seen from the supporting factors of the formulation and ratification of local regulations, participation in legislative sessions, communication with constituents, responsiveness to community needs. While the inhibiting factors, namely the availability of skilled human resources, complete facilities and infrastructure, information, and experience are openly conveyed and have been optimized as they should.The findings of this study can be used as a basis for improving the effectiveness of the performance of legislative members in meeting the satisfaction of the community/constituents.